Parental Control: the Relationship Amongst Parental Supervision, Education, Income and Children’s Viewing Habits - Dinkha, Juliet; Mitchell, Charles; Zogheib, Bashar (American Journal of Humanities and Social Sciences, 2014)
This paper explores children’s relationship with TV and influence of parental mediation on that relationship by examining factors such as parents’ income, marital status, age, education, religion and the effects of the child’s time spent with nannies. We employed the Parents Topline study by Luntz, Maslansky Strategic Research and Hart Research (2007) to investigate children's relationship with parents/guardians and television consumption in Kuwait. After pre-testing the survey was modified and several questions were omitted and altered to align it with the cultural factors and variables and was then translated into Arabic. In total, 827, surveys were deemed valid of which, 56.3% were females, and 43.7 % were males. Statistical significant variables were found in parental age, marital status, and domestic help and socioeconomic status and nationality in our results. Additionally what was found was that the socioeconomic status of the parents had no significance in parental mediation of their children’s TV consumption habits as much as age and education of the parent and age of the child.